2021
DOI: 10.3390/ijms22031317
|View full text |Cite
|
Sign up to set email alerts
|

Changes Induced by Mind–Body Intervention Including Epigenetic Marks and Its Effects on Diabetes

Abstract: Studies have evidenced that epigenetic marks associated with type 2 diabetes (T2D) can be inherited from parents or acquired through fetal and early-life events, as well as through lifelong environments or lifestyles, which can increase the risk of diabetes in adulthood. However, epigenetic modifications are reversible, and can be altered through proper intervention, thus mitigating the risk factors of T2D. Mind–body intervention (MBI) refers to interventions like meditation, yoga, and qigong, which deal with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 155 publications
0
7
0
3
Order By: Relevance
“…After excluding duplicates, 366 articles (PubMed 105, Cochrane 122, and Google Scholar 139 articles) were assessed for its eligibility from three different databases and 45 articles[ 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 ] [ Figure 1 , Tables 1 and 2 ] were included in the final scoping review.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicates, 366 articles (PubMed 105, Cochrane 122, and Google Scholar 139 articles) were assessed for its eligibility from three different databases and 45 articles[ 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 ] [ Figure 1 , Tables 1 and 2 ] were included in the final scoping review.…”
Section: Resultsmentioning
confidence: 99%
“…Existe evidencia de que las terapias basadas en mindfulness inducen cambios biológicos positivos en los sistemas nervioso, cardiovascular, inmunológico y hormonal, lo cual explica el auge de este tipo de aproximaciones como terapias complementarias en el manejo de patologías relacionadas con los sistemas mencionados (29, [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][48][49][50][51][52][54][55][56][57][58][59][60][61][62][63][64][65][66]69,70).…”
Section: Discussionunclassified
“…Mendioroz et al (citados en 58) encontraron cambios en la longitud telomérica, secundarios a la metilación de genes en meditadores a largo plazo versus individuos sin experiencia en meditación. La longitud de los telómeros de los individuos con experiencia en meditación se relacionó con una mayor metilación del gen GPR31 (gen encargado de activar el factor de transcripción NF-κB), porque disminuyeron la producción de citocinas proinflamatorias (58).…”
Section: Mecanismos Inmunológicosunclassified
“…A systematic review of RCT investigates the positive role of yoga on the HPA axis, sympathetic nervous system, cortisol, and anxiety (57). Many studies also demonstrated yogic practices play a potential role in diabetes by reducing different risk factors such as stress, anxiety depression, cortisol secretion, inflammation, cortisol, and blood glucose level (58,59). The yogic practices also activate the parasympathetic nervous system, lower anxiety, stress, and insulin resistance, which may be associated with improvement of general health status and overall QOL (59,60,61,62).…”
Section: Discussionmentioning
confidence: 99%